Factors associated with alcohol consumption among medical cannabis patients with chronic pain. (February 2018) - Davis, Alan K.; Walton, Maureen A.; Bohnert, Kipling M.; Bourque, Carrie; Ilgen, Mark A.
Abstract: Introduction: Chronic pain is the most common reason for medical cannabis certification. Data regarding alcohol use and risky drinking among medical cannabis patients with pain is largely unknown. Therefore, we examined the prevalence and correlates of alcohol use and risky drinking in this population. Methods: Participants completed surveys regarding demographics, pain-related variables, anxiety, cannabis use, and past six-month alcohol consumption. Alcohol use groups were defined using the AUDIT-C [i.e., non-drinkers, low-risk drinkers, and high-risk drinkers (≥ 4 for men and ≥ 3 for women)] and compared on demographic characteristics, pain measures, anxiety, and cannabis use. Results: Overall, 42% (n = 330/780) were non-drinkers, 32% (n = 251/780) were low-risk drinkers, and 26% (n = 199/780) were high-risk drinkers. Compared to non-drinkers, low- and high-risk drinkers were significantly younger whereas a larger proportion of low-risk drinkers reported being African-American compared to non- or high-risk drinkers. High-risk drinkers reported significantly lower pain severity/interference compared to the other groups; high-risk drinkers were also less likely to be on disability compared to other groups. A multinomial logistic regression showed that patients reporting lower pain severity and less disability had greater odds of being classified a high-risk drinker. Conclusions: High-risk drinking appears common among medical cannabis patients. Future research should examine whether such use is concurrent or consecutive, and the relationship of such co-use patterns to consequences. Nevertheless, individuals treating patients reporting medical cannabis use for pain should consider alcohol consumption, with data needed regarding the efficacy of brief alcohol interventions among medical cannabis patients. Highlights: Among chronic pain patients using medical cannabis, 26% were high-risk drinkers Those with less pain severity/disability had greater odds of being a high-risk drinker. Providers should assess alcohol consumption among patients using medical cannabis. Future studies should examine the efficacy of alcohol interventions in this population.